Estratégia de geração de barramentos CC simétricos isolados, para inversores NPC, com conversor CC-CC trifásico série ressonante - Natume, Humberto Kazuo (2016)
This work presents the analysis and practical implementation of the three-phase resonant series CC-CC converter operating in ZCS mode. The structure of this converter has been modified in order to generate a DC bus insulated at high frequency with symmetrically divided voltages. Based on the theory of multipulse rectifiers, the Graetz bridge of the output stage of the DC-DC converter has been replaced by two full-bridge three-phase rectifiers connected in series. The isolating transformer also needed changes, in the sense of feeding these rectifiers in isolation, giving independence to the operation of the same. As a result, each of the rectifier outputs was stapled to a voltage proportional to the drive voltage, without the use of controllers. In this respect, the objective of generating a symmetrical bus, suitable for feeding NPC multilevel inverters, was fully satisfied. It has been shown that the strategy of generating a bus with symmetrically divided voltages can be extended to inverters with more than three levels, in the case of the NPC. All theoretical results were confirmed by the implementation of a 2 kW prototype that achieved an efficiency of over 95%.